Advancing the study of stateness in Central America: methodology and some illustrative findings - Vargas Cullell, Jorge (Revista de Ciencia Política, 2019)
This paper succintly describes how a network of researchers associated to the Costa Rican Programa Estado de la Nación developed new data sources and crafted direct measures of stateness for the Central America countries. Our theoretical framework relied on Mann’s concept of state infrastructural power. As a result, a wealth of information is now available to scholars studying stateness in Central America, as well as to researchers engaged on broader comparative research about stateness in Latin America. Some preliminary findings are reported and guidelines for future research are suggested.